(untitled) (Papeles, 2012)
The following article discusses the relevance of the Afro-Colombian Studies to Colombian education and how it can be worked in the classroom from the methodology of project work. In order to advocate for inclusive education and the recognition of multiculturalism Colombian and tending to eradicate racial discrimination in educational institutions.